Book review: Francesco Pastore, The Youth Experience Gap. Explaining National Differences in the School-to-work Transition - PAŞNICU, Daniela (Annals of Spiru Haret University. Economic Series, 2016)
Francesco Pastore is qualified as full professor of Economic Policy. Currently, he is Assistant Professor of Economics at Seconda Universita di Napoli. He is also secretary of the Italian Association of Labor Economics (AIEL) and a member of the executive board of the Italian Association of Comparative Economic Studies (AISSEC). His main research interests are in labor and education economics. He is also interested in development and transition economics. He has contributed extensively in several such fields as regional unemployment differentials, school-to-work transitions, labor market dynamics, gender discrimination, human capital investment, public employment services and passive as well as active labor market policy, labor market consequences of international trade and nonprofit organization.